Mix of products from the company "Confiteca" - Granda Ortega, Nevis; Andrade Baculima, Héctor; Castro Lliguisaca, Cristian; Lasso López, Linda (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
The purpose of this research was to analyze the mix of products and the website of Confiteca, an Ecuadorian company dedicated to the manufacture and commercialization of confectionery. This is a review article, in which several aspects were considered that must do both with merchandising and the product portfolio, such as width, depth, length and consistency, the methodology applied is based on the bibliographic and comparative method, since criteria from various authors and experts were taken, in which a decision rule and a traffic light were defined for the respective analysis. As results it was verified which is the mix with which it counts and which type of merchandising is applied in each part of it, as well as conclusions it was defined that the company has defined segments and it shows them in each presentation of its products, the weaknesses that exist in its page Web and respectively in the mix.